Design and simulation on the air dam for Proton Pesona by using CFD tool - Ahmad Sapuan, Hasan (2008)
This project was carried out to design aerodynamic and efficient front air dam for Proton Persona car. In carrying this project, the objective is to compare the car stability for Proton Persona car with and without air dam. The whole process will involve designing, matching, simulation approach and comparison the data. Airflow around vehicle can affect many aspects of vehicle performance including vehicle drag, vehicle lift and down force. Vehicle lift and down force can affect the vehicle stability and handling. This air dam was design to reduce lift force and improve the turbulent air flow underneath Proton Persona car. The design is refer to the market journal and market also. The dimension gets from the model vehicle scanning by 3D Scanner. Than sketch the base line of air dam in Solidwork. Besides that, prepare the model vehicle in software environments for simulation process. This thesis focus on design of air dam and how it will affect to the underbody flow. The simulation is comparing the vehicle model with and without air dam base pressure distribution. The result will be compare on pressure distribution underbody. The air dam will affect the lift force on the front Proton Persona when moving in high speed. However, the height of air dam must suitable with road requirement to avoid damage to air dam when driving in rough road surface.